2016
DOI: 10.1017/ice.2016.261
|View full text |Cite
|
Sign up to set email alerts
|

Top 1% of Inpatients Administered Antimicrobial Agents Comprising 50% of Expenditures: A Descriptive Study and Opportunities for Stewardship Intervention

Abstract: OBJECTIVE To characterize the top 1% of inpatients who contributed to the 6-month antimicrobial budget in a tertiary, academic medical center and identify cost-effective intervention opportunities targeting high-cost antimicrobial utilization. DESIGN Retrospective cohort study. PATIENTS Top 1% of the antimicrobial budget from July 1 through December 31, 2014. METHODS Patients were identified through a pharmacy billing database. Baseline characteristics were collected through a retrospective medical chart revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…7 One study demonstrated that 80% of patients in an acute-care hospital accounting for the top 1% of drug expenditures were followed by ID consulting services, and more than half of these had opportunities for cost-effective stewardship interventions. 9 Antimicrobial stewardship programs should collaborate with ID consultants in coordinating optimal, cost-effective, and guideline-adherent pharmacotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…7 One study demonstrated that 80% of patients in an acute-care hospital accounting for the top 1% of drug expenditures were followed by ID consulting services, and more than half of these had opportunities for cost-effective stewardship interventions. 9 Antimicrobial stewardship programs should collaborate with ID consultants in coordinating optimal, cost-effective, and guideline-adherent pharmacotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Curbing the use of anti-MRSA agents in the hospital is of interest due to resistance, toxicity, and cost concerns, and daptomycin is a particular target. [6][7][8] As part of a new Joint Commission Standard, antimicrobial stewardship programs and hospitals are required to track antibiotic prescription, to implement prescriber education, and to report antibiotic utilization data back to the prescribers. 9 Therefore, a reliable measure for tracking and reporting is important.…”
Section: Discussionmentioning
confidence: 99%
“…They may also offer the potential to provide higher-quality, more costeffective care to vulnerable patients, similar to ASP programs in other health care settings. 37,38 Implementation of ASPs in jails and prisons, however, is a short-term solution to help improve the conditions of confinement. In parallel, we support legislative and policy reforms that seek to address and reverse the harms of incarceration.…”
Section: Figure Applying Bioethical Principles To Antimicrobial Presc...mentioning
confidence: 99%